A comparative handbook to the gospels of Matthew and Luke: comparisons with pseudepigrapha, the Qumran scrolls, and Rabbinic literature - Chilton, Bruce (The New Testament gospels in their Judaic contexts, 2021)
Apocrypha, pseudepigrapha, Philo and Josephus -- The Dead Sea scrolls -- The Rabbinic canon -- The Targumim.